Dissecting R gene and host genetic background effect on the Brassica napus defense response to Leptosphaeria maculans - Haddadi, Parham (Sci Rep, 2019)
While our understanding of the genetics underlying the Brassica-Leptosphaeria pathosystem has advanced greatly in the last decade, differences in molecular responses due to interaction between resistance genes and host genetic background has not been studied. We applied RNAseq technology to monitor the transcriptome profiles of Brassica napus (Bn) lines carrying one of four blackleg R genes (Rlm2, Rlm3, LepR1 & LepR2) in Topas or Westar background, during the early stages of infection by a Leptosphaeria maculans (Lm) isolate carrying the corresponding Avr genes. We observed upregulation of host genes involved in hormone signalling, cell wall thickening, response to chitin and glucosinolate production in all R gene lines at 3 day after inoculation (dai) albeit having higher level of expression in LepR1 and Rlm2 than in Rlm3 and LepR2 lines. Bn-SOBIR1 (Suppressor Of BIR1-1), a receptor like kinase (RLK) that forms complex receptor like proteins (RLPs) was highly expressed in LepR1 and Rlm2 at 3 dai. In contrast Bn-SOBIR1 induction was low in Rlm3 line, which could indicate that Rlm3 may function independent of SOBIR1. Expression of Salicylic acid (SA) related defense was enhanced in LepR1 and Rlm2 at 3 dai. In contrast to SA, expression of Bn genes with homology to PDF1.2, a jasmonic acid (JA) pathway marker, were increased in all Rlm and LepR lines at 6 and 9 dai. Effect of host genetic background on induction of defense, was determined by comparison of LepR1 and LepR2 in Topas vs Westar genotype (i.e. T-LepR1 vs W-LepR1 and T-LepR2 vs W-LepR2). In both cases (regardless of R gene) overall number of defense related genes at the earliest time point (3 dai) was higher in Tops compared to Westar. SA and JA markers genes such as PR1 and PDF1.2 were more induced in Topas compared to Westar introgression lines at this time point. Even in the absence of any R gene, effect of Topas genotype in enhanced defense, was also evident by the induction of PDF1.2 that started at a low level at 3 dai and peaked at 6 and 9 dai, while no induction in Westar genotype was observed at any of these time points. Overall, variation in time and intensity of expression of genes related to defense, was clearly dependent on both R gene and the host genotype.